CYBER NOTARY DALAM PELAKSANAAN JABATAN NOTARIS BERKAITAN DENGAN PKR PERSEROAN TERBATAS DI INDONESIA - Raendhi Rahmadi; Retno Susilowati (Fakultas Hukum Universitas Islam Syekh Yusuf, 2023)
A notary as a public official has a position in one district or city with an office area the size of one province according to the position of the office, where the notary can carry out his position in that office area for every job throughout Indonesia. This applies as long as it is carried out within the area of his office by appearing in front of him when carrying out legal actions. The pandemic period caused by Covid-19 has changed many aspects of life, including people's mobility and this has changed new habits where sometimes people are reluctant to meet face to face directly and instead switch to meeting virtually in meetings or making legal decisions within the company so that things This creates a new culture in decision making that needs to be adjusted by Notaries as public officials. Notary regulations relating to making virtual deeds are a necessity, this concept has been put forward in the Cyber Notary concept, which was previously hampered by non-compliance with regulations. In this research, the author carried out a juridical analysis which was explained descriptively analytically using primary data obtained from the experience of several business actors during the pandemic, where the cyber notary concept can provide convenience for visitors and better protection, because it has consistency in authenticating documents and information that meets the Principle of Accuracy in the position of notary. Keyword :Cyber Notary, , Kebiasaan Baru, Autentifikasi